ANALISIS PENYALAHGUNAAN RHODAMIN B PADA LIPTINT YANG BEREDAR DI KOTA BENGKULU MENGGUNAKAN METODE KROMATOGRAFI LAPIS TIPIS DAN SPEKTROFOTOMETRI UV-VIS - Ramadhani, Oktalia; Mulia, Putri; Danang Kurniawan, Tri; Intan Perma Sari , Rose; Kurnia Putri, Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Liptint is a popular cosmetic product because it gives lips a natural color. However, some products still contain hazardous substances such as Rhodamine B, which is toxic and carcinogenic. This study aimed to detect the presence of and measure the levels of Rhodamine B in lip tints sold in several markets in Bengkulu City. A total of 15 samples were analyzed. Qualitative analysis was performed using Thin-Layer Chromatography (TLC), while quantitative analysis utilized UV-Vis Spectrophotometry. TLC test results indicated that two samples (PM3 and PK3) tested positive for Rhodamine B, as evidenced by Rf values close to the standard and fluorescence under UV light. Meanwhile, the results of quantitative analysis at a maximum wavelength of 542.95 nm showed Rhodamine B levels of 0.0332% in sample PM3 and 0.0129% in sample PK3. Based on the results obtained, it can be concluded that lip tints testing positive for Rhodamine B are not permitted for distribution in the market in accordance with the Regulation of the Head of the Food and Drug Supervisory Agency, and that Rhodamine B has highly dangerous effects if used over the long term.